Organ-specific accumulation of microplastics in Holothuria atra Jaeger, 1833 (Holothuriidae) from Kepulauan Seribu, Indonesia - Hanum Isfaeni; Reza Dino Mahardika; Samuel Darell Tohonan Sihite; Muhammad Naufal Al Ghazali; Keenan Garcianov Lasamahu; Ardestia Dwi Alindra Syahrial; Siti Muthi’ah Fairuz Saniyyah; Unaisah Syahidah; Riyani Yahya; Ahmad Dwi Susilo (Bioma, 2026)
Microplastics represent a major threat to tropical marine ecosystems in Indonesia. This study investigated the spatial and organ-specific accumulation of microplastics in Holothuria atra collected from Pulau Tidung Kecil and Pari, Kepulauan Seribu. A total of 28 individuals were analyzed by separating the tentacles, skin, and digestive tract, followed by hydrogen peroxide degradation, density separation, stereomicroscopy, and polymer identification using Fourier Transform Infrared (FTIR) spectroscopy. Statistical analysis was performed with a Gamma Generalised Linear Model (GLM) and Tukey post hoc tests at α = 0.05. Microplastics were detected in all examined organs at both sampling locations. Three microplastic types were identified—fragments, fibres, and pellets—with fragments being the most abundant. The highest microplastic concentration occurred in the digestive tract, particularly in specimens from Pulau Tidung Kecil. GLM analysis showed that island location, body part, and microplastic type significantly influenced microplastic abundance (p < 0.05). FTIR analysis revealed the predominance of polyethylene (PE) and polypropylene (PP), suggesting contamination sources linked to domestic waste and fishing activities. These findings highlight the susceptibility of Holothuria atra to microplastic exposure and suggest its potential utility in monitoring microplastic pollution in tropical coastal ecosystems.